UNA REVALUACIÓN Y APROXIMACIONES A LA INTERPRETACIÓN DEL CALENDARIO MÍTICO CEREMONIAL MOCHE BASADO EN LA ICONOGRAFÍA DE LOS TEMAS COMPLEJOS DE LA HUACA CAO VIEJO, COMPLEJO EL BRUJO, COSTA NORTE DEL PERÚ - Franco Jordán, Régulo (2017)
The complex themes belong to a polychrome relief made from mud located in two pre-Hispanic temples that belong to Moche Culture in the northern coast of Peru dated circa VII century AD. This is an extraordinary symbolic and artistic representation found in the last XX century. This iconographic composition is the result of the strong change of attitude within the Moche society as an answer to the climate crisis. This new attitude implied the instauration of a new order to confront the chaos and the installation of a new mythical-ceremonial calendar represented in these two murals with complex themes. This article focuses on an iconographic study and on the use of etnohistorical sources to approach its importance.